2011
DOI: 10.1111/j.1365-2796.2011.02381.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation inAPOA1predicts increased risk of ischaemic heart disease and total mortality without low HDL cholesterol levels

Abstract: .  Haase CL, Frikke‐Schmidt R, Nordestgaard BG, Kateifides AK, Kardassis D, Nielsen LB, Andersen CB, Køber L, Johnsen AH, Grande P, Zannis VI, Tybjærg‐Hansen A (Copenhagen University Hospitals and Faculty of Health Sciences, University of Copenhagen, Denmark; University of Crete Medical School, Heraklion, Greece; Whitaker Cardiovascular Institute, Boston University School of Medicine, Boston, MA, USA). Mutation in APOA1 predicts increased risk of ischaemic heart disease and total mortality without low HDL chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 27 publications
3
44
0
Order By: Relevance
“…However, this was not the case: after contrasting findings, 14 recent large-scale studies dissecting the genetic architecture of lipid metabolism showed that increased low-density lipoprotein (LDL) cholesterol and triglyceride levels seem to be causally related to cardiovascular risk, but this was not the case for HDL cholesterol levels. 1517 This is in line with interventional trials with CETP (cholesteryl ester transfer protein) inhibitors that increased HDL cholesterol by >100% but did not decrease cardiovascular outcomes. 18 It is now widely accepted consensus that HDL cholesterol rather represents a surrogate marker that does probably not properly reflect real HDL functionality.…”
supporting
confidence: 68%
“…However, this was not the case: after contrasting findings, 14 recent large-scale studies dissecting the genetic architecture of lipid metabolism showed that increased low-density lipoprotein (LDL) cholesterol and triglyceride levels seem to be causally related to cardiovascular risk, but this was not the case for HDL cholesterol levels. 1517 This is in line with interventional trials with CETP (cholesteryl ester transfer protein) inhibitors that increased HDL cholesterol by >100% but did not decrease cardiovascular outcomes. 18 It is now widely accepted consensus that HDL cholesterol rather represents a surrogate marker that does probably not properly reflect real HDL functionality.…”
supporting
confidence: 68%
“…Similar but not identical phenotypes were produced by expressing the bioengineered apoA-I[R160V/H162A] and apoA-I[R149A] mutants and the naturally occurring mutants apoA-I[R151C] Paris and apoA-I[L144R] Zaragosa (Haase et al 2011;Chroni et al 2005a;Koukos et al 2007b). This phenotype could be corrected by co-expression of the mutant with human LCAT.…”
Section: Apoa-i Mutations That Affect Apoa-i/lcat Interactionsmentioning
confidence: 96%
“…67 For the effect of rare variants on CAD risk, the picture is complicated by the fact that some rare variants in APOA1 that associate with low HDL cholesterol, cause amyloidosis, and this, in addition to other symptoms, may manifest as CAD due to small vessel disease, increased intima media thickness, or in later stages as cardiomyopathy. Haase et al 68,69 resequenced the APOA1 gene in >10 000 individuals, genotyped the identified variants in >55 000 individuals from the general population, and reported that the apparent increased risk associated with nonsynonymous mutations in APOA1 became insignificant when variants previously associated with amyloidosis were removed from the analysis. In support, mutations in APOA1 reported to associate with endothelial dysfunction, increased arterial wall thickness, and premature coronary heart disease 70 have more recently been shown to cause systemic amyloidosis.…”
Section: Mendelian Randomizationmentioning
confidence: 99%